Imām al-Baghawī (d. 516/1123): Tafsīr and Sunnism during the 11th-12th Centuries in Khurāsān - Hassanein, Nourhan (AUC Knowledge Fountain, 2024)
A number of recent studies have focused on the intellectual trends and debates surrounding the formation of Sunnism in the 11-12th centuries. Academics have explored various currents within the intellectual and social context of Sunni Islam during the 11th-12th centuries. George Makdisi, Richard Bulliet, Jonathan Brown, Daphna Ephrat, Mohamed Eissa, and Ahmad Khan studied topics related to the educational system, the scholarly community, heresy and Sunni orthodoxy, legal studies, ḥadīth, and theology. However, the status of scholarship on works of tafsīr differs significantly. There are few studies concentrated on the classical period, such as works on the commentaries of al-Thaʿlabī (d. 427/1035), al-Wāḥidī (d.468/1078), and al-Zamakhsharī (d. 538/1144). This thesis aims to build upon these existing studies by focusing on a hitherto unstudied Qurʾān commentary written by al-Ḥusayn b. Masʿūd b. Muḥammad al-Baghawī (d. 516/1123), a prolific writer in three principal disciplines of Sunnism. The central aim of this thesis is to comprehensively examine and assess the impact of al-Baghawī’s Qurʾān commentary, titled "Maʿālim al-tanzīl," on the intellectual landscape of Sunnism during the 11th-12th centuries in Khurāsān. It will contend that "Maʿālim al-tanzīl" serves as a pivotal nexus in shaping the development of Qurʾānic interpretation during this period, owing to its active participation in Sunni intellectual discourses surrounding ḥadīth and Islamic jurisprudence.